The Making of Character through Local Culture: Scrutinizing the Madihin Tradition in the Banjar Community - Abdillah, Muhammad Torieq; Budiarti, Erlita; Fikrianoor, Ardiyan; Fatmawati, Amelia; Wahdini, Muhammad (Institut Agama Islam Negeri Kerinci, 2023)
Numerous incidents and reports concerning behaviors deviating from societal norms have marred the nation's character. One of the causes is the orientation of education itself, which predominantly focuses on cognitive aspects. Therefore, it is crucial to establish a new educational paradigm based on character education. The objective of this research is to understand how the local art form of Madihin can be implemented as a new paradigm in education, serving as a learning tool through the wisdom embedded in it to shape a cultured and charactered society. The research employs a qualitative descriptive approach with field research. The findings reveal that Madihin can serve as a learning tool with cultural significance. The implementation of Madihin as a learning tool to shape a cultured and charactered society can be provided to the community in the form of: First, serving as 'moral excellence' within the Madihin verses themselves to shape character through the development of virtues that have meaning in life. Secord, focusing on soft skills to maintain noble cultural values and cultivate a holistic mindset. Third, providing knowledge about character with cultural education as the basis for daily behavior. Keywords: Learning Tool, Madihin, Cultural, Character Education